Implementation of Mathematics Learning in the Semester Credit System Implementation in Senior High School State 1 Jember - Citra Wahyuningtyas; Susanto Susanto; Erfan Yudianto (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
This study aims to describe the profile of the implementation of mathematics learning in the class, the challenges that the teachers did, and the efforts which did is to overcome the challenges in the credit semester system in mathematics learning activities. The research subjects are the students and mathematics teachers of X class in SMA 1 Jember. Data collection methods used documentation, observation, and interview. Based on the results of research that can be proven by mathematical learning in the implementation of the Credit Semester System described based on learning planning, learning activities, and the authentic answer. The mathematics teacher make a preparation by compiling lesson plans that guided by the 2013 Curriculum RPP and compiling the UKBM that adapted to appropriate scientific indicators. In the implementation of learning, the teacher carries out learning activities by applying scientific request. The assessment also adjusted to the 2013 Curriculum indicators. The teacher's assessment consisted of the preparation of the Credit Semester System, students' readiness, and conversation. Efforts which did is to overcome these challenges are by conducting socialization and MGMP as well as providing motivation and stimulus to students while conducting learning activities.